'Banks 1 – Portugal 0'? Financial player entanglements in the Eurozone crisis. (July 2021) - Stadheim, Victoria B-G
The euro has been at the heart of the debate about the crisis in the Eurozone. For some, it represents a fixed exchange rate regime, which hampered peripheral countries' competitiveness, and for others, the European Monetary Union has a 'flawed institutional design' and an insufficient degree of integration that engendered the crisis. The present article analyses monetary integration from a materialist perspective. It draws attention to political agency, power and crisis management. The article focuses on the case of Portugal and poses the question of how the country's authorities were compelled to request a rescue package from the International Monetary Fund, the European Central Bank and the European Commission in 2011. It shows that this decision was triggered by the political agency of a series of players within the world of finance, most notably Portugal's domestic banks, the independent Bank of Portugal and the European Central Bank. Reflecting their material interconnection through the European monetary system, their agency was highly coordinated. The strategies for crisis management that came to deepen the recession were not the result of insufficient European integration – they rather reflected Portugal's form of integration within the European Monetary Union at the specific moment of crisis.